2021
DOI: 10.3899/jrheum.201623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Rheumatology Practice in Latin America

Abstract: Objective To describe the impact of COVID-19 pandemic on Latin American rheumatologists from a professional, economic, and occupational point of view. Methods We conducted an observational cross-sectional study using an online survey sent to rheumatologists of each non-English-speaking country member of the Pan American League of Rheumatology Associations (PANLAR). A specific questionnaire was developed. Results Our survey included 1097 rheumatologists from 19 Latin American countries. Median (IQR) age of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
1
16
1
1
Order By: Relevance
“…This is potentially supported by our finding that German physicians believed that management changes would not persist, because changes might have begun to revert by the time of our survey. Surveys in Latin America and the UK that showed similar telemedicine utilization during the pandemic to our study showed that lower proportions of rheumatologists believed that telemedicine would continue [ 22 , 23 ]. In particular, a UK study conducted during August–December 2020 showed that the majority of rheumatologists believed that <50% of follow-up appointments post-pandemic would be conducted remotely; although still high, this could potentially indicate a cooling of opinions about telemedicine after the initial pandemic peak [ 22 ].…”
Section: Discussionsupporting
confidence: 62%
“…This is potentially supported by our finding that German physicians believed that management changes would not persist, because changes might have begun to revert by the time of our survey. Surveys in Latin America and the UK that showed similar telemedicine utilization during the pandemic to our study showed that lower proportions of rheumatologists believed that telemedicine would continue [ 22 , 23 ]. In particular, a UK study conducted during August–December 2020 showed that the majority of rheumatologists believed that <50% of follow-up appointments post-pandemic would be conducted remotely; although still high, this could potentially indicate a cooling of opinions about telemedicine after the initial pandemic peak [ 22 ].…”
Section: Discussionsupporting
confidence: 62%
“…[9][10][11] Moreover, direct faceto-face patient encounters in Latin America declined during pandemic-related public health mandates. 12 The pandemic has also led to a shift in healthcare delivery methods, with the expansion of telemedicine. 13 One study from the US reported an increase in telemedicine uptake within rheumatology to 41.4% of all follow-up encounters early in the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio de Fernández-Ávila et al, donde se encuestaron a 1.097 reumatólogos de 19 países de América Latina, con un 81,8% de los participantes perteneciente al ámbito privado, se informó una reducción de casi el 60% en las jornadas presenciales de trabajo, con una fuerte impronta de la telemedicina desarrollada por el 78% de los encuestados. Dentro de las diferentes tecnologías mencionadas, las más frecuentes fueron: las videoconsultas (50,6%), las consultas telefónicas (45,5%) y la mensajería electrónica (Whatsapp en un 38,5%) 8 .…”
Section: Discussionunclassified